Strategi Pemasaran Toko Sanamisi dalam Meningkatkan Penjualan Produk; Analisis Ekonomi Syariah - Irianti Irianti; Aslan Aslan (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2025)
This study aims to analyze the marketing strategies implemented by Toko Sanamisi to increase product sales and to evaluate their compliance with the principles of Islamic economics. The research approach employs a qualitative method with an empirical legal study, relying on primary data obtained through direct interviews with the store owner, employees, and customers, as well as secondary data from scholarly journals published in the past ten years. The results indicate that Toko Sanamisi's marketing strategies—which include social media promotion, personalized customer service, utilization of digital marketplaces, and customer loyalty programs—have successfully increased transaction volume and customer satisfaction. From the perspective of Islamic economics, these strategies reflect the principles of Islamic commercial ethics (muamalah), such as information transparency, honesty, and ethical service, thereby positioning marketing activities not only as profit-oriented but also as a means of attaining blessings and fulfilling spiritual values in business.